Desain Model Kolaborasi Multidisipliner Perguruan Tinggi-Sekolah dalam Penguatan Literasi Nasional Berbasis Bahasa, Sastra, Pendidikan Inklusif, dan Literasi Digital - Hesti; Musiman; Idawati; Carla Maretha; Ratna Tri Utami (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the need for collaboration between universities and schools in strengthening national literacy and to design a multidisciplinary collaboration model that supports the development of 21st-century skills in students. The study used a descriptive qualitative approach involving two high schools: a public school and an inclusive school, as well as university lecturers involved in the literacy mentoring program. Data were collected through literature review, observation, in-depth interviews, and documentation. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing, and was strengthened by triangulation of sources and methods to maintain data validity. The results show that collaboration between universities and schools still faces various obstacles, such as limited sustainable programs, low digital literacy integration, and a suboptimal multidisciplinary approach to learning. This study resulted in a design for a multidisciplinary collaboration model based on language, literature, inclusive education, and digital literacy that is contextual and applicable. This model is expected to strengthen the school's literacy culture while supporting the development of critical thinking, creativity, communication, and collaboration skills in students